Analisis Intertekstualitas di Relief Candi Prambanan Makna Fisik Wanita - Ade Onny Siagian; Hadion Wijoyo (Universitas Gadjah Mada, 2022)
The existence of women, especially regarding their physical beauty and beauty, is not a myth found in works of art or literature, including those found in temple reliefs. Many temple reliefs in Indonesia depict women and their exoticism, both physically and their activities and position in society. Prambanan Temple is a temple that is known to be closely related to the figure of a beautiful woman named Roro Jongrang who occupies the main statue. In addition to the main statue, on the reliefs of the walls of Prambanan Temple there are also reliefs about other women. This relief is a text that describes women and their existence. This study seeks to explore and interpret the physical woman on the wall reliefs of Prambanan Temple. The research was conducted by using semiotic-semanalytic analysis of Juli Kristeva. The results of the intertextual research show that almost all of the women's physical relief panels at Prambanan Temple are constructed to read the signs on the reliefs as a text, so that the story or story conveyed can be easily recognized and understood. The meaning of genotext in the context of women on temple wall reliefs who appear without a physical cover or naked is a common thing or a habit in society based on geographical and social conditions. The upper physical nudity of women at that time did not affect the views of the people around, especially men. Because women are chosen not based on their body shape but other attractions that are sometimes mystical. The meaning of phenotext, women who appear naked has a negative meaning and leads to pornography, can cause unlimited male attraction, can become victims of sexual crimes, and can even be in contact with the law.